2020
DOI: 10.1177/1947603520942941
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fluid Biomarkers in Knee Osteoarthritis: A Systematic Review and Quantitative Evaluation Using BIPEDs Criteria

Abstract: Objective The aim of this systematic review was to analyze the evidence about the efficacy of the several synovial fluid (SF) biomarkers proposed for knee osteoarthritis (OA), categorizing them by both molecular characteristics and clinical use according to the BIPEDs criteria, to provide a comprehensive and structured overview of the current literature. Design A systematic review was performed in May 2020 on PubMed, Cochrane Library, and Embase databases about SF biomarkers in patients with knee OA. The searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 176 publications
0
43
0
1
Order By: Relevance
“…24 Notably, while recent meta-analyses demonstrated that elevated MMP-3 is a consistent diagnostic marker for osteoarthritis, these have cast doubt on whether MMP-3 levels alone reliably correlate with osteoarthritis severity. 7 Subsequently, some studies report the ratio of MMP-3 to TIMP-1 expression to evaluate changes in metalloproteinase-mediated cartilage damage. 11,33,51 Our analysis demonstrated a significant increase in the MMP-3 to TIMP-1 ratio during the acute postinjury period.…”
Section: Discussionmentioning
confidence: 99%
“…24 Notably, while recent meta-analyses demonstrated that elevated MMP-3 is a consistent diagnostic marker for osteoarthritis, these have cast doubt on whether MMP-3 levels alone reliably correlate with osteoarthritis severity. 7 Subsequently, some studies report the ratio of MMP-3 to TIMP-1 expression to evaluate changes in metalloproteinase-mediated cartilage damage. 11,33,51 Our analysis demonstrated a significant increase in the MMP-3 to TIMP-1 ratio during the acute postinjury period.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that tissue viability could be maintained during the culture period. Cartilage of these explants presented a similar inflammatory response like in human OA joints with respect to findings of histology, gene expression, and analysis of supernatant conditioned medium (Martel-Pelletier et al, 2016;Robinson et al, 2016;Boffa et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…In 6 of the 7 studies, there was a significantly positive correlation between osteoarthritis severity and VEGF. 91 …”
Section: Vascular Epithelial Growth Factor (Vegf)mentioning
confidence: 99%